PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS ALAT PERAGA MANIPULATIF TERHADAP PEMAHAMAN KONSEP MATEMATIKA DAN RASA PERCAYA DIRI SISWA - Muhamad Azis; Murtono Murtono; Suad Suad (Universitas Muria Kudus, 2021)
The purpose of the study was to analyze the effectiveness of the Problem Based Learning model based on manipulative teaching aids on the understanding of mathematical concepts and the self-confidence of elementary school students.The research method used is experimental research methods. The research design used is a pre-experimental one group pre-test-posttest design. In this study, the sample was grade VI SDN 1 Kangkung Demak students. The independent variable in this study is Problem Based Learning with manipulative teaching aids and the dependent variable is understanding mathematical concepts and students' self-confidence. Data collection uses observation to obtain data about students' self-confidence. The researcher used a questionnaire/questionnaire technique to obtain data on the PBL learning model with manipulative teaching aids in mathematics. The test instrument is in the form of a description of 10 questions, meanwhile a questionnaire is used to collect research data about the level of students' self-confidence.The results showed that based on the t-test, the t-value was 23,359, while the t-table with df=43 was 2.0195, the t-count t-table (23,359 2.0195), which means that the PBL model based on manipulative teaching aids is effectively used to increase the self-confidence of elementary school students. The effectiveness of PBL learning based on manipulative teaching aids is proven to increase students' understanding of mathematical concepts and self-confidence.